I'll Ride The Wave Where it Takes Me: A Cyberethnography of Pearl Jam Fan Communities - Peter Hornberger (Adult Education Research Conference, 2016)
This roundtable explores the learning processes of adult fans of the music group Pearl Jam and their potential development of critical consciousness. The confluence of popular culture, music, fan culture, and digital media that occurs within these fan spaces is rich for exploration of contemporary forms of critical public pedagogy.
Keywords: popular culture; critical public pedagogy; cyberethnography